Association of vitamin D receptor gene polymorphisms with breast cancer risk in an Egyptian population - Haidan M El-Shorbagy; Nada H Mahmoud; Salwa Sabet (Tumor Biology)
This study aimed to explore whether genetic polymorphisms in vitamin D receptor are correlated to the breast cancer prevalence in an Egyptian population. Polymerase chain reaction–restriction fragment polymorphism was used to genotype three frequently analyzed vitamin D receptor gene single-nucleotide polymorphisms (rs1544410, rs7975232, and rs731236) and were identified by sequencing analysis. This is the first study that recorded a new single-nucleotide polymorphism in ApaI genotype within an Egyptian population and was registered with the accession number KY859868. The authors found that TC in rs731236, and TG in KY859868 single-nucleotide polymorphism showed significant distribution differences with an increased risk of breast cancer ( p  < 0.05, odds ratio = 3.71, 95% confidence interval: 1.04–13.28 and p  < 0.001, odds ratio = 7.05, 95% confidence interval: 2.02–24, respectively) compared with the wild-type TT genotype carriers in both single-nucleotide polymorphisms. In addition, the distribution frequencies of haplotypes ACT, GTT, and ATT in the patients group were significant, where ATT haplotype was associated with the highest breast cancer risk among all other haplotypes in the patients group ( p  = 0.0023, odds ratio = 1.72, 95% confidence interval: 1.24–2.437). In conclusion, vitamin D receptors ApaI and TaqI confer high breast cancer susceptibility, particularly in Egyptians females carrying haplotype ATT. However, further studies focusing on the vitamin D receptor variants and haplotypes effects on vitamin D and vitamin D receptor concentrations, activities, and functionalities are needed.